Multi-criteria evaluation of BI systems. The case study of InKoM dashboard - Dyczkowski, Mirosław; Korczak, Jerzy; Dudycz, Helena (Business Informatics, 2014)
The article presents an approach to evaluate the BI systems applied in the InKoM project. The evaluation method is based on a scorecard framework, oriented towards Decision Support Systems and projects dedicated to the management supporting of small and medium enterprises (SME). To design the method, known existing BI maturity models, usability standards, and scorecard frameworks have been analyzed and adapted to SMEs area. Notably, the scorecard framework was extended to the new evaluation criteria associated with innovative functions created in the InKoM project, especially such as ontologies of economic and financial knowledge, and visual navigation and exploratory interface based on topic maps. The selected elements of the scorecard framework and usage in InKoM of multi-criteria evaluation are illustrated and discussed in this paper
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 46-60
Keywords: BI system evaluation; intelligent dashboard; scorecard framework; InKoM project; ewaluacja systemu BI; inteligentny kokpit menedżerski; ramowa karta wyników; projekt InKoM